Dynamic Interactions among Boundaries and the Expansion of Sustainable Aquaculture - Broitman, Bernardo R.; Halpern, Benjamin S.; Gelcich, Stefan; Lardies, Marco A.; Vargas, Cristian A.; Vásquez-Lavín, Felipe; Widdicombe, Stephen; Birchenough, Silvana N. R. (Frontiers in Marine Science, 2017)
Aquaculture is the fastest growing food production system in the world, generating more than half of the global seafood harvested today. These type of activities are crucial to provide key nutritional components for humanity in the future as populations worldwide are increasing and the demands for securing food resources are imperative. Multiple socio-ecological factors such as weak regulations and focus on maximizing production limit production and threaten the sustainable growth of aquaculture. We present a novel policy framework to evaluate and pursue growth in aquaculture considering four boundaries: biological productivity, environmental constraints to that productivity, policy that inhibits or promotes different kinds of aquaculture, and social preferences that determine aquaculture markets. Using a range of scenarios, we have shown that sustainable growth in aquaculture requires simultaneous consideration of all four boundaries and the potential interactions between all of these options. Our proposed conceptual framework shows that to further expand the boundaries of aquaculture production, the policy focus must remain flexible to enable the adaptation of from single-boundary approaches. Our approach takes account of the current boundaries, helping to consider the adaptive policy, which is deemed as a necessary tool for considering the dynamic interactions among boundaries, thus addressing the problem of defining the evolving limits of sustainable aquaculture.